ANALISIS POTENSI HUTAN TANAMAN JABON (Anthocephalus cadamba Miq) - Sari, Ema Tiana; Hamzari, Hamzari (Jurnal Warta Rimba, 2021)
Jabon (Anthocephalus cadamba Miq) is an endemic plant in Sulawesi and Maluku, this species is classified as a fast growing plant with high economic value and its distribution is distributed naturally throughout Indonesia. This study aims to determine the potential of Jabon Plantation Forest aged 4 and 5 years. This research was conducted for two months in Wulai Village, Bambalamotu District, Pasangkayu Regency, West Sulawesi Province and in Rerang Village, Dampelas District, Donggala Regency, Central Sulawesi Province. This research was determined by purposive sampling using line plot sampling where the plot is made with a square shape with a sampling intensity of 10%. Based on the results of the study showed the average standing volume of the age of 4 years was 92.71 m³ / Ha with a standard deviation value of 13.74 m³ / Ha, the deviation obtained from the variance value was 188.84 m³ / Ha. The standard error value is 6.48 m³ / Ha with an accuracy obtained (large) of 6.99%. While the average volume of the age of 5 years is 209.45 m³ / Ha with a standard deviation value of 16.39 m³ / Ha, the deviation obtained from the variance value is 268.64 m³ / H. The standard error value is obtained 6.95 m³ / Ha with accuracy obtained (small) 3.32%. The degree of deviation and accuracy of the data obtained is strongly influenced by the amount of sampling intensity.Keywords: analysis, potential, Jabon.